Safety of Chinese Cabbage Waste and Rice Straw Mixed Silage and Its Effect on Growth and Health Performance of Hu Sheep - Zhiqi Lu; Chuang Li; Lie Hou; Zhenbin Zhang; Yue Lu; Chun Xue; Ruxin Qi; Muhammad Hammad Zafar; Jun Xu; Mengzhi Wang (Fermentation, 2024)
Improper disposal of vegetable waste can cause serious environmental pollution, but because they contain huge water content and organic matter, they are not suitable for disposal by methods such as incineration and landfill. However, vegetable waste contains a large amount of nutrients and have some complementary effects with rice straw in terms of physical structure, nutrients, and moisture. In this experiment, the plant feed (corn husk, peanut shells and sorghum shells) was used as the control group (CON group), and the mixed silage of Chinese cabbage waste and rice straw (mixed silage) was used as the experiment group (TRE group), and its safety performance was evaluated by testing its toxin content, pesticide residues, vitamin contents and feeding experiment of Hu sheep. In the animal experiment, 16 healthy Hu sheep (5.5 months, 39.11 ± 4.16 kg) were randomly divided into two groups of 8 each. The results of the safety performance evaluation showed that the content of mycotoxins, heavy metals, and nitrites as well as pesticide residues in the crude feeds of both groups were within the range of Chinese feed hygiene standards. In addition, the levels of deoxynivalenol (DON) and aflatoxin (AFT) in the CON group were lower, while the content of ochratoxin (OTA) and zearalenone were higher than those in the TRE group (p < 0.05). The levels of plumbum(Pb), chromium (Cr), cadmium (Cd), and nitrite in the CON group were lower than the mixed silage, while the levels of As were higher than the mixed silage (p < 0.05). It is worth noticing that the content of vitamin B2 (VB2) and vitamin C (VC) in the TRE group was higher than the CON group (p < 0.05). The results of the feeding experiment showed that the mixed silage did not affect the growth performance, nutrient digestibility, organ index, and intestinal index of Hu sheep (p > 0.05). In addition, the mixed silage reduced the weight of omasum, the proportion of omasum to live weight before slaughter, the amount of compound stomach, and the proportion of compound stomach to live weight before slaughter, which were higher than those in the TRE group (p < 0.05). The thickness of the basal layer of the rumen abdominal sac, the red blood cell count, the content of IL-10, and TNF-α in the blood, and TNF-α content in the rumen of the Hu sheep in the TRE group were higher than the CON group (p < 0.05). In conclusion, the feed safety index content of the mixed silage did not exceed the Chinese feed hygiene and safety standards and did not cause adverse effects on the growth performance of the Hu sheep, and it improved the immune performance of the body and digestive tract of the sheep to a certain extent and promoted the healthy development of the sheep.